PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SMP NEGERI 2 INUMAN - Ernayeti Ernayeti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study is a classroom action research conducted at SMP Negeri 2 Inuman, this study aims to improve thelearning outcomes of integrated IPS class VIII of SMP Negeri 2 Inuman. This research was conducted twocycles by applying contextual teaching and learning model. The results of research indicate that the learningoutcomes have increased each cycle. In the first cycle of meeting I, teacher activity got score 14 (46,42%), oncycle I meeting II 17 (60,71%), in cycle II meeting I equal to 21 (75,00%). And on second cycle of meeting IIwith score 24 (85,71%). At the first meeting I cycle activity of student get score 15 (53,57%), at meeting II cycleII get 19 (67,86%), at meeting I cycle II get 21 (75,00%). And at meeting II cycle with score 23 (82,14%). On thebasic score of the number of students who completed is 12 students, the UH I amounted to 17 students and at UHII numbered 23 students. In the basic score of student learning results obtained a value of 56.78. At UH Iobtained 67,25 and at UH II got 79,68.